2013
DOI: 10.1002/pssa.201228442
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced polarization switching in ferroelectric Bi0.5Na0.5TiO3 single crystals by defect control

Abstract: Single crystals of ferroelectric (Bi,Na)TiO 3 (BNT) were grown by the top-seeded solution growth (TSSG) method at a high oxygen pressure of 0.9 MPa using Pt crucibles and their conductivity (leakage current) and polarization properties were investigated at 25 8C along h100i cubic . The platinum concentration ([Pt]) in BNT crystals was controlled by using different kinds of Na salts in flux. It is shown that the conductivity of BNT crystals is governed by Bi vacancies for crystals with a [Pt] less than approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The direction of E, i.e., the axis normal to the crystal plates was set to be along the <001> pc direction. SR-XRD data were collected with a transmission geometry using a large cylindrical two-dimensional imaging plate (IP) camera with a 1/4χ three-axis goniometer at BL02B1 in the SPring-8 synchrotron radiation facility [50][51][52][53]. A high SR energy of 35 keV [wavelength: 0.035313(2) nm for BNT and 0.035345(2) nm for BNT-5%BT] was adopted so that X-rays with a high transmission ratio could penetrate through the crystals and that a high-angle diffraction pattern could be observed.…”
Section: Methodsmentioning
confidence: 99%
“…The direction of E, i.e., the axis normal to the crystal plates was set to be along the <001> pc direction. SR-XRD data were collected with a transmission geometry using a large cylindrical two-dimensional imaging plate (IP) camera with a 1/4χ three-axis goniometer at BL02B1 in the SPring-8 synchrotron radiation facility [50][51][52][53]. A high SR energy of 35 keV [wavelength: 0.035313(2) nm for BNT and 0.035345(2) nm for BNT-5%BT] was adopted so that X-rays with a high transmission ratio could penetrate through the crystals and that a high-angle diffraction pattern could be observed.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that Na 2 CO 3 promotes a dissolution of Pt from the Pt crucible into the solution, resulting in a higher [Pt] and that the [Pt] value in BNT crystals can be controlled by the Na 2 CO 3 content in the flux used for crystal growth processes. [21] These results suggest that the Pt impurity plays a partial role in the defect structure in the BNT crystals. Pöykkö and Chadi [22] have suggested that Pt is substituted at the Ti 4+ site in PbTiO 3 as Pt 2+ (Pt Ti ″ )…”
Section: Resultsmentioning
confidence: 89%
“…These particles were found to cause no significant influence upon the electrical properties of the crystal. 86) The compositions of the crystals were analyzed by X-ray fluorescence (XRF), showing that the both crystals obtained by the two methods have a BMN composition (x) of 4%. Hereafter, the crystals are denoted by the Po 2 during the crystal growth, i.e., the flux method by 'Po 2 = 0.02 MPa' and the high-Po 2 TSSG method by 'Po 2 = 0.9 MPa'.…”
Section: Methodsmentioning
confidence: 99%